An activity-based microsimulation model of travel demand in the Jakarta metropolitan area - Sadayuki Yagi; Abolfazl Kouros Mohannadian (Journal of Choice Modelling, 2010)
The goal of the study reported in this paper was to develop a comprehensive activity-based modeling system in the context of developing countries, providing accurate estimates which are expected to serve as better inputs for evaluation of different transportation policy scenarios. The case study is Jakarta, Indonesia as one of the largest metropolitan areas in Asia. The modeling system primarily adopts a tour-based structure in which the tour is used as the unit of modeling travel instead of the trip, preserving a consistency in destination, mode, and time of day choices across trips.
Keywords: 330; activity-based models; tour-based models; microsimulation; Jakarta metropolitan area; developing countries